The impact of the cognitive dimensions of the physical education and sports teacher on developing sports and health culture among first-year secondary students - Larachi, Mohamed; Zeraoula, Ali; Nasr, Ouyhia (The International tax journal, 2026)
The study aimed to identify the impact of the cognitive level of specialized physical education teachers on improving the health cultural level of students? The descriptive method was used, employing two instruments: a questionnaire and a cognitive dimensions scale, applied to a sample of 120 individuals. The study concluded that teachers contribute to the development of sports and health culture. It also recommended strengthening and updating teachers’ cognitive background and preparing a book that clarifies the cognitive aspects that should be taught to students?